Thrombosed Aneurysm of Superficial Epigastric Vein Simulating Inguinal Hernia: Report of Two Cases - Eleni Skandalou; Panagiotis Papadopoulos; Marianthi Kavelidou; Stavros Kalfadis; Theodoros Tzigkalidis; Ioannis Skandalos (Case Reports in Vascular Medicine)
Aim. Presentation of two cases of superficial epigastric vein aneurysm simulating inguinal hernia. To our knowledge, only one other case is reported in the literature. Case presentation. The first case was a 34-year-old female with left inguinal pain and swelling which was clinically diagnosed as inguinal hernia. The second case was a 28-year-old female with inguinal pain and swelling, depicted with triplex ultrasonography and computed tomography, and was suspected to have inguinal hernia or enlarged inguinal lymph node. During the surgical exploration, both patients were found to have thrombosed aneurysm of the superficial epigastric vein. During the surgical exploration, both patients were found to have thrombosed aneurysm of the superficial epigastric vein. The superficial epigastric vein was ligated, and the venous aneurysms (6×4×3 and 2×3×2.5 cm, respectively) were excised. Histological examination of the thrombosed aneurysm showed complete replacement of the vascular wall by fibrous tissue, thrombosis, and an inflammatory reaction. There were no postoperative complications, and both patients were discharged on the second postoperative day. The 3-month and 1-year follow-up examination, respectively, was uneventful. Conclusion. Although venous aneurysms in the inguinal area are rare, they should be included in the differential diagnosis of a groin swelling.